Temperature and non-communicable diseases: Evidence from Indonesia's primary health care system - Manuela Fritz (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2021)
Increasing ambient temperatures will severely affect human health in the decades to come and will exacerbate a variety of chronic health conditions. In this paper, I examine the temperaturemorbidity relationship in the tropical climate environment of Indonesia with a focus on chronic, non-communicable diseases, namely diabetes, cardiovascular and respiratory diseases. Drawing on detailed individual level data from the Indonesian national health insurance scheme JKN and linking it with meteorological data on daily temperature realizations on a fine spatial level, I estimate the effect of high ambient temperatures on the daily number of primary health care visits. Exploiting the panel structure of the data and using a distributed lag model, I find that all-cause, diabetes and cardiovascular disease morbidity substantially increase at days with high mean temperatures. Specifically, on a day with a mean temperature above 29.5êC, the daily visits for diabetes and cardiovascular diseases increase by 29% and 19%, respectively, and these increases are permanent and not offset by visit displacement. Contrarily, I do not find any effects on respiratory disease morbidity. Heterogeneity analyses suggest that elderly and women suffer more severely from high temperatures. Back-of-the-envelope cost calculations indicate a substantial financial burden for the Indonesian health care system due to increasing temperatures.
Keywords: I10; I13; I18; Q50; Q51; Q54; 330; Health; Non-Communicable Diseases; Temperature; Climate Change; Indonesia